2018
DOI: 10.1016/j.learninstruc.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Girls get smart, boys get smug: Historical changes in gender differences in math, literacy, and academic social comparison and achievement

Abstract: Girls' lack of self-belief has frequently been cited as a major barrier to advancement in both empirical research and in the popular imagination. With girls now outcompeting boys at almost every educational level, this paper considers if girls still have lower self-concept than boys, if this changes when controlling for academic ability, and what mechanisms explain gender differences. We compare and contrast rational choice, contrast, and assimilation approaches to self-concept and juxtapose historical traject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 53 publications
5
29
0
2
Order By: Relevance
“…This result supports the findings from a study which showed that while female students scored higher in self-efficacy related to language and arts than male students, male students tend to exhibit higher self-efficacy than their counterpart in mathematics [28]. Female students' lower self-efficacy has become an obstacle for them to advance in the mathematics related discipline [28], [29]. The result of this study suggests that more encouragement related activities in class may help female students to thrive better in learning mathematics.…”
Section: Resultssupporting
confidence: 87%
“…This result supports the findings from a study which showed that while female students scored higher in self-efficacy related to language and arts than male students, male students tend to exhibit higher self-efficacy than their counterpart in mathematics [28]. Female students' lower self-efficacy has become an obstacle for them to advance in the mathematics related discipline [28], [29]. The result of this study suggests that more encouragement related activities in class may help female students to thrive better in learning mathematics.…”
Section: Resultssupporting
confidence: 87%
“…The results related to Research Question 2 indicated that boys had higher scores in mathematics self-concept than girls in both achievement groups. This result is aligned with findings from larger studies which indicate reduced feelings of efficacy and competence in girls relative to boys when considering mathematics as a subject (Hyde, 2015;Parker, Van Zanden, & Parker, 2018;Sax, Kanny, Riggers-Pieh, Whang, & Paulson, 2015). Previous studies have shown mathematics self-concept to be a predictive factor in subsequent mathematics course selections (OECD, 2012;McPhan, Morony, Pegg, Cooksey, & Lynch, 2008).…”
Section: Discussionsupporting
confidence: 83%
“…Educational statistics and worldwide media have reported a clear gender gap in academic achievement between males and females with boys lagging behind girls in terms of subject grades, secondary school graduation, and tertiary level enrollment and completion (Clark, Lee, Goodman, & Yacco, 2008;Parker, Van Zanden, & Parker, 2018). Researchers Majzub and Rais (2010) argue that male underachievement is a topic of critical importance both in Malaysia and around the world.…”
Section: A Global Perspectivementioning
confidence: 99%